Selective optogenetic stimulation of the retrotrapezoid nucleus in sleeping rats activates breathing without changing blood pressure or causing arousal or sighs - Burke, Peter G. R. (2015)
Combined optogenetic activation of the retrotrapezoid nucleus (RTN; a CO2/proton-activated brainstem nucleus) with nearby catecholaminergic neurons (C1 and A5), or selective C1 neuron stimulation, increases blood pressure (BP) and breathing, causes arousal from non-rapid eye movement (non-REM) sleep, and triggers sighs. Here we wished to determine which of these physiological responses are elicited when RTN neurons are selectively activated. The left rostral RTN and nearby A5 neurons were transduced with channelrhodopsin-2 (ChR2+) using a lentiviral vector. Very few C1 cells were transduced. BP, breathing, EEG, and neck EMG were monitored. During non-REM sleep, photostimulation of ChR2+ neurons (20s, 2-20 Hz) instantly increased V̇e without changing BP (13 rats). V̇e and BP were unaffected by light in nine control (ChR2−) rats. Photostimulation produced no sighs and caused arousal (EEG desynchronization) more frequently in ChR2+ than ChR2− rats (62 ± 5% of trials vs. 25 ± 2%; P < 0.0001). Six ChR2+ rats then received spinal injections of a saporin-based toxin that spared RTN neurons but destroyed surrounding catecholaminergic neurons. Photostimulation of the ChR2+ neurons produced the same ventilatory stimulation before and after lesion, but arousal was no longer elicited. Overall (all ChR2+ rats combined), ΔV̇e correlated with the number of ChR2+ RTN neurons whereas arousal probability correlated with the number of ChR2+ catecholaminergic neurons. In conclusion, RTN neurons activate breathing powerfully and, unlike the C1 cells, have minimal effects on BP and have a weak arousal capability at best. A5 neuron stimulation produces little effect on breathing and BP but does appear to facilitate arousal.